KESULITAN BELAJAR MENULIS PADA SISWA KELAS II SEKOLAH DASAR - Agusta Kurniati; Yohanes Berkhmas Mulyadi; Ita Puspita Sari (STKIP Persada Khatulistiwa Sintang, 2020)
This study aims to description about learning difficulties in writing of students class II at Sekolah Dasar Negeri 02 Lanjak. This is a qualitative within case study research. The tools used are observation sheets, interviews, and documentations. The results of this study was the writing is not legible such as writing too ugly, writing too italic and the form of letters or numbers is not readable. The results of this study indicate that there are several factors that cause children to have difficulty learning to write i.e: a) lack of attention and motivation from parents in overcoming children's writing difficulties; b) children do not have self-awareness in writing and do not memorize the letters of the alphabet; c) children also do not have the awareness and learning responsibilities; d) lack of school collaboration with parents in overcoming difficulties in learning writing. Teachers and parents efforts to overcome children learning difficulties in writing i.e: a) always providing motivation and encouragement to children so that the spirit of learning to write; b) take an individual approach to children who have difficulty learning to write, to find out the wishes of children; c) provide guidance such as additional instruction at the end of study or after school; d) collaborate between schools and parents to overcome difficulties in learning writing.